Of the plants and their images: of the shapes and colors of the world, of the shapes and colors of artists (Palíndromo, 2024)
This article has as its motto the relationship between plants and images. To this end, it starts with the writings of the Italian philosopher and image theorist Emanuel Coccia. It discusses the uses of images by the natural sciences, as well as the ways in which the arts presented the images of a vegetal world. Different images of plants and landscapes were then analyzed, such as: the botanical illustrations from the 19th century, the Renaissance paintings by Leonardo Da Vinci and the Dutch ones by Johannes Vermeer. Finally, the central issue of plant images is discussed and analyzed in the work of two contemporary Brazilian artists, Walmor Corrêa and Adriana Varejão.
Keywords: landscape paintings; plant images; Emanuel Coccia